347 Read the First Page: An Audit on Medicine Reconciliation in General Surgery Inpatients at London District General Hospital. (12th October 2021) - Vutipongsatorn, K; Patel, P; Prakash, A; Musawi, J. Al
Abstract: Aim: Medication-related incidents occur more frequently when medicine reconciliation happens more than 24 hours after admission. The National Institute for Health and Care Excellence recommends a complete reconciliation within 24 hours of admission. General Surgery is a busy specialty with a high patient turnover rate. Hence, this audit was conducted to assess the extent of a problem and mitigate it. Method: Every adult General Surgery inpatient who were admitted for over 24 hours were included. Patients on intensive care or high dependency unit were excluded. Drug charts were reviewed every Thursday for nine weeks between October and December 2020. Data from the first three weeks were used to establish baseline. Three interventions were introduced, each lasting two weeks. Any significant harm to patients due to incomplete reconciliation was recorded. Results: At baseline (n = 100), 38.0% of patients had incomplete reconciliation. This significantly reduced to 23.4% (n = 64, p-value=0.037) between Weeks 4 and 5 after baseline data was presented at a team meeting and posters were put up. Allowing pharmacists to flag up missing medications on a daily job's list did not significantly reduce the incompletion rate (23.0%, n = 74, p-value>0.999). Finally, performing a medicine reconciliation ward round on Weeks 8 and 9 further reduced the incompletion rate to 2.8% (n = 74, p-value=0.001). One significant harm was noted on Week 1. Conclusions: Medicine reconciliation is a vital aspect of patient safety. Raising awareness of the issue significantly reduced the incompletion rate. However, the most effective intervention is conducting a medicine reconciliation ward round.